"I've been a whizz-kid since I've been at college": Giving voice to the collective memories of adults with learning disabilities about the role that technology has played in their lives - Jane Seale; Ajay Choksi; Karen Spencer (Disability Studies Quarterly, 2019)
The focus of this paper is the history of technology use by people with learning disabilities in the UK in the late twentieth century and the impact that technology has had on the lives of people with learning disabilities. A methodological framework, underpinned by the principles of inclusivity, transparency and reciprocity was employed to enable eight adults with learning disabilities to share their memories of using technologies, from childhood to the present day. Our analysis of these histories challenge notions of deficit, dependency and inequality that are traditionally associated with people with learning disabilities.